Implementation of marketing strategies in the process of formation and representation of ukrainian national identity - Kurguzov, Andriy (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The urgency of the topic under study is conditioned by the current necessity of preserving and forming the Ukrainian national-cultural identity, raising the level of national consciousness of Ukraine’s citizens, and representing the national-cultural identity of our country to the global community.The aim of the article is to study the phenomenon of Ukrainian national identity and to identify the specific features of its formation in the context of modern language-cultural dynamics; to provide the analysis of the possibilities of practical use of modern marketing strategies in the process of representing Ukrainian national identity and to outline the prospects for the development of Ukrainian national identity as well as the ways of representing the national-cultural identity of our country in the current conditions of competition between different language and cultural systems.Design/methodology/approach. The realization of goals and objectives prompted the implementation of the following general scientific methods and principles: the method of system analysis, structural and functional analysis, the method of axiological interpretation, the analytical method.Findings. The necessity of systematic consolidation of activities of the state, public structures and associations as well as individual citizens of Ukraine and the Ukrainian diaspora in the process of preservation and development of Ukrainian national identity and the use of ways of representing the national-cultural identity of our country in the conditions of global competition of different linguistic and cultural systems is manifested.Research implications. The research provides the further directions for the implementation of modern marketing strategies in the process of representing Ukrainian national identity to the global community considering the specifics of the modern language-cultural dynamics.Originality/value. The scientific significance of the given research lies in the revealing the modern peculiarities of the formation and preservation of the Ukrainian national identity to the global community in conditions of the existing language-cultural dynamics; provides the results of the analysis of the possibilities of practical use of marketing strategies in the process of formation and representation of the Ukrainian national identity.